Case report: Radical robotic nephroureterectomy after chemotherapy followed by avelumab in a patient with node-positive UTUC - Studentova, Hana; Student, Vladimir; Kurfurstova, Daniela; Kopova, Andrea; Melichar, Bohuslav (Frontiers in Oncology, 2024)
IntroductionPlatinum-based chemotherapy followed by the immune checkpoint inhibitor avelumab represents an intensified upfront therapy regimen that may result in significant downstaging and, subsequently, potentially radical robotic nephroureterectomy with a lymph node dissection, an uncommon approach with an unexpectedly favorable outcome.Case presentationWe report a case of a 70-year-old female presented with a sizeable cN2+ tumor of the left renal pelvis and achieved deep partial radiologic response after systemic therapy with four cycles of gemcitabine-cisplatin chemotherapy followed by avelumab maintenance therapy and subsequent robotic resection of the tumor. The patient continued with adjuvant nivolumab therapy once recovered after surgery and remained tumor-free on the subsequent follow-up. The systemic treatment was without any severe adverse reaction.ConclusionWe highlight the feasibility of the upfront systemic therapy with four cycles of gemcitabine-cisplatin chemotherapy followed by avelumab maintenance, robotic-assisted removal of the tumor, and adjuvant immunotherapy with nivolumab. This intensification of the upfront systemic therapy, and the actual treatment sequence significantly increase the chances of prolonged survival or even a cure. This type of personalized therapeutic approach can accelerate future advanced immunotherapeutic strategies.